Agroecology publications and coloniality of knowledge (2013)
ABSTRACT : Agroecology is a recent scientific field that has become increasingly active since 1990. It has moved away from conventional emphasis on crops and productivity and has embraced a systemic, multidisciplinary approach that focuses on agroecosystems or food systems and their sustainability. Here, we analyze original articles in agroecology that have been published in eight major global databases in order to establish where agroecology is taking place and what topics focus on agroecology. For this, a systematic review was conducted with original articles with the word “agroecological” in the title and published in English, Spanish, and/or Portuguese as inclusion criteria. One hundred thirty-one articles were found but we were able to access 116. Area of study, country of affiliation of the researchers, publication countries, and topic of the paper were analyzed. It was found that Brazil (18 articles out of 131), Cuba (8), and Nigeria (8) are the most studied countries; Brazil (19 in 116 articles), the USA (12), and Cuba (9) are the countries with more affiliated researchers; and the Netherlands (26 out of 131), Brazil (19), and Germany (12) are the countries that publish articles the most. Additionally, it was found that the most popular topics of research are behavior of crops and species in function of environmental conditions (15 out of 116), soils (12), and production in agro- ecological systems (13), while sustainability (3), agroecological transition (1), and biodiversity (1) are rare. Our findings show that research follows a colonial pattern where industrialized countries lead publishing, conduct research studies both in industrialized and non-industrialized countries, and do not publish in non-industrialized countries, while non-industrialized countries publish in industrialized and non-industrialized countries and do not conduct research studies in foreign regions. In addition, they show that food systems and sustainability are still not common subjects of study although they are main concerns in agroecology.